Problematika Kedudukan Direktur yang Merupakan Penjamin Perorangan (Personal Guarantee) sebagai Termohon PKPU Problems of the Position of Directors Who Are Individual Guarantor (Personal Guarantee) as Respondents in PKPU - Manullang, Wanako Bicton (JURNAL HUKUM SEHASEN, 2026)
This study aims to determine the legal position of directors in debt agreements accompanied by personal guarantees. In this study, the method used is doctrinal research, which means a literature study in which the author intends to use existing legal materials or secondary data. The conclusion that can be obtained is that the position of a guarantor in the Debt Payment Suspension (PKPU) process is essentially the last layer when the main debtor is no longer able to fulfill their debt payment obligations. Legally, although the guarantor bears subsidiary obligations like the debtor, the main purpose of PKPU is to provide the main debtor with the opportunity to restructure the debt through a peace plan, not to carry out direct collection.